The incorporation of toys in the public library an evaluation study - Bagunu, Jessie Rose M. (2002)
The objectives of this study were to determine the propriety of incorporating toys in the Quezon City Public Library; to evaluate the developmental effectiveness of toys in the library where children are able to manipulate and play with them and to know the problems encountered with the inclusion of toys in the library.